2011
DOI: 10.1590/s0004-282x2011000400020
|View full text |Cite
|
Sign up to set email alerts
|

Application of International Classification of Functioning, Disability and Health (ICF) in individuals with spinal cord injury

Abstract: After spinal cord injury is common functionality is affected. Objective: To evaluate the functionality of patients with spinal cord injury. Method: Cross-sectional study by means of the International Classification of Functionality (ICF). 109 adults with spinal cord injury in the city of Curitiba, Brazil were evaluated. Results: The categories most compromised in body were intestines and bladder, sexuality, energy, sleep, emotion and weight. In the domain activities and participation, there was greater difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 11 publications
2
21
0
14
Order By: Relevance
“…As for education level these studies showed the predominance of education level lower than 10 years of study, with its significance, ASA (p = 0.046); MIF (p > 0.05) and IB (p = 0611). In other studies, in different contexts, it is observed the predominance of SCI in young men, aged between 20 and 40 years [15]- [18]. This fact confirm data obtained in this study showed that 87.8% of people with spinal cord injury were males with a prevalence of 63.5% under the age of 40 years and the average age was 36.62 years (SD = 13.74).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As for education level these studies showed the predominance of education level lower than 10 years of study, with its significance, ASA (p = 0.046); MIF (p > 0.05) and IB (p = 0611). In other studies, in different contexts, it is observed the predominance of SCI in young men, aged between 20 and 40 years [15]- [18]. This fact confirm data obtained in this study showed that 87.8% of people with spinal cord injury were males with a prevalence of 63.5% under the age of 40 years and the average age was 36.62 years (SD = 13.74).…”
Section: Discussionsupporting
confidence: 91%
“…These indicators consistent with the literature by showing that mostly victims of spinal cord injury are men affected in their most productive years, this fact can be explained because of the etiology of traumatic injuries, mainly due to the growing number of accidents and violence which young men are more exposed [18]- [21].…”
Section: Discussionsupporting
confidence: 89%
“…It is important to note that people with irreversible physical disabilities remain with the same International Classification of Diseases (ICD), however, they do not remain with the same functionality classification. 21 After spinal or neurological damage an individual may suffer various functional changes.…”
mentioning
confidence: 99%
“…21,3 Nurses need to understand the rehabilitation not only as a process of recovery of motor function, but as an auxiliary mechanism for this patient to achieve the highest possible level of physical, spiritual and self-esteem functioning, even if this evolution occurs only in intrinsic levels. 5 Therefore, it is necessary knowledge and understanding of its essential elements and their applicability, requiring of these professionals specific knowledge and expertise of both the multidimensional aspects of quadriplegia, as the correct use of ICF and ICD classification.…”
mentioning
confidence: 99%
“…Many aspects of the activities and participation can be evaluated, such as precision of movements, time required to execute them, and the occurrence and severity of errors. However, the final outcome for most rehabilitation services is functional independence 3 , for this is related to personal values, family determinants 4,5 , and is usually associated with social participation, especially in less developed countries where environmental factors act predominantly as barriers 6 . The first scales to measure such damage focused mainly in physical examination and radiological imaging.…”
mentioning
confidence: 99%